A Research about the Chinese Terminology in Viaje de la China by Adriano de las Cortes - Zhihong, Xu (Sinología hispánica. China Studies Review, 2022)
This paper examines and researches the origin of the Chinese terms Spanishized by Adriano de las Cortes in Viaje de la China to refer to local objects or personal names from various Asian languages. Since there are certain errors in previous research, this article would be important not only to understand better this single work, but to understand many western works of that time on China, considering the fact that Westerners shared transliterations of many words of Chinese origin in their communications.